Etiology, clinical profile and short-term outcome of acute kidney injury in children at a tertiary care pediatric nephrology center in Pakistan. (1st January 2017) - Tresa, Vina; Yaseen, Afshan; Lanewala, Ali Asghar; Hashmi, Seema; Khatri, Sabeeta; Ali, Irshad; Mubarak, Muhammed
Abstract: Background: The reported prevalence rates and etiologies of acute kidney injury (AKI) are quite variable in different regions of the world. The current study was planned to determine the etiology, clinical profile, and short-term outcome of pediatric AKI at our hospital. Methods: A prospective, observational study was carried out from April 2014 to March 2015. All pediatric patients (1 month to ≤15 years) diagnosed as AKI using modified pRIFLE criteria were studied and followed for 3 months to document short-term outcome. Results: AKI was diagnosed in 116 children. The mean age was 7.5 ± 4.4 years and males were predominant (60.3%). At presentation, 83.6% had oliguria/anuria, 37.1% hypertension and 17.2% severe anemia. Etiology included primary renal (74/116; 63.8%), postrenal (28/116; 24.1%) and prerenal (11/116; 9.5%) causes. Postinfectious glomerulonephritis (PIGN) and crescentic glomerulonephritis in primary renal, obstructive urolithiasis in postrenal and sepsis in prerenal, were the most common etiologies. At presentation, 89/116 (76.7%) patients were in pRIFLE Failure category. Regarding outcome, 68 (58.6%) patients recovered, six (5.2%) died, 18 (15.5%) developed chronic kidney disease (CKD) and 22 (19%) end-stage renal disease (ESRD). Comparison of recovered and unrecovered AKI showed that characteristics such as hypertension, severe anemia, edema, volume overload, requirement of mechanical ventilation, initiation of dialysis and need of >5 sessions of dialysis had statistically significant ( p  <0.05) association with nonrecovery. Conclusion: Glomerulonephritides (PIGN and crescentic) and obstructive urolithiasis are major causes of pediatric AKI at our center. A fairly high percentage of cases recovered and these mainly comprised of PIGN and obstructive urolithiasis.